Examining the Use of Simulation in Nursing Education and Enhancing Clinical Capability - 1Khizra Ehsan Ellahi, 2Iram Anwar, 3Hadeel Alreshidi, 4Dr Rukhsana Ghulam Nabi, 5Syeda Asma Rasalat, 6Naseer Ahmed Mirani, 7Khurram Shahzad, 8Kashif Lodhi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
In contemporary nursing education, the integration of simulation techniques has garnered significant attention as a means to augment clinical competence and serious thinking skills amongst nursing students. Recognizing the evolving healthcare landscape and the need for proficient and adaptable nurses, this study delves into the utilization of simulation in nursing education, aiming to uncover their effect on enhancing clinical competencies and fostering critical thinking abilities. Aim: The main goal of our current research is to explore effectiveness of simulation in nursing education and its potential to elevate clinical competence and critical thinking skills. Through a comprehensive analysis, the study aims to discern the specific aspects of simulation that contribute most significantly to the development of these essential attributes in nursing students. Methods: This research adopts the mixed-methods approach, incorporating both quantitative and qualitative methodologies. Surveys and assessments will be administered to a diverse sample of nursing students, evaluating their clinical competencies and serious thinking abilities before and after experience to simulation-based education. Additionally, qualitative data will be gathered through interviews and focus group discussions, providing deeper insights into the subjective experiences and perceptions of participants. Results: Preliminary findings indicate a positive correlation between the incorporation of simulation in nursing education and enhancement of clinical competencies and critical thinking skills. Quantitative data reveals statistically significant improvements, while qualitative insights offer a nuanced understanding of the psychological and practical benefits experienced by students engaged in simulation-based learning. The results underscore the potential of simulation as the valuable pedagogical tool in nursing education. Conclusion: Our current research contributes valuable insights into efficacy of simulation in nursing education, shedding light on its potential to elevate clinical competencies and critical thinking skills among students. The findings suggest that the integration of simulation should be considered as an essential component of nursing curricula, providing a dynamic and experiential learning environment that mirrors real-world clinical scenarios. As nursing education continues to evolve, embracing innovative approaches such as simulation can play a pivotal role in preparing future healthcare professionals for the challenges of contemporary healthcare settings.